Short-range order in high entropy alloys: Thermodynamic modeling and application to Nb-Ti-V-Zr system - Kumar, Shanker (IIT(BHU) Varanasi, 2023)
Abstract is available in the attachment.
Keywords: Metallurgical Engineering